Attitude of the Kremlin towards “heresy” shown by J. Paleckis in 1946–1950 - Pocius, Mindaugas (Genocidas ir rezistencija, 2017)
The aim of this article is, referring to the documents from Russian State Archive of Social Political History and other sources, to reveal how the leaders of the Central Committee of the All-Soviet Union Communist party (bolsheviks) and officers from the Central Committee apparatus valued manifestations of national communism demonstrated by J. Paleckis and his conflicts concerning the issues of sovietization of Lithuania with A. Sniečkus. The other purpose of this paper is to find out whether J. Paleckis, emphasizing specific conditions in Lithuania and wishing to mitigate the course of sovietization, received any support from the leaders in the Kremlin; why A. Sniečkus, who used to criticize J. Paleckis, did not try to remove him from the Politburo of the Central Committee of the Lithuanian Communist Party or dismiss him from the position of the chairman of the Presidium of the Supreme Council of Lithuanian Soviet Socialist Republic. This article presents efforts made by J. Paleckis in order to find allies in Moscow, establish patron-client type relationship with Andrei Zhdanov, a secretary of the Central Committee of the All-Soviet Union Communist party (bolsheviks). The analysis of the sources allows us to draw some conclusions. It could be maintained that the secretaries of the Central Committee of the All-Soviet Union Communist party (bolsheviks) and leaders of divisions of the Central Committee apparatus closely watched the conflict displayed between J. Paleckis and A. Sniečkus and the majority of the Politburo of the Central Committee of the Lithuanian Communist party (bolsheviks) led by the latter. These communists were anxious for unhealthy working climate in the Central Committee of the Lithuanian Communist party (bolsheviks). J. Paleckis‘s political conflicts were caused by manifestation of his national communism ideology, tendency to take care of local interests and his intersection with strict Marxist classic position taken by A. Sniečkus and by majority of other members of the Politburo of the Central Committee of the Lithuanian Communist party (bolsheviks). It could be stated that political “heresy” of J. Paleckis, who was involved into a risky political games behind the scenes in order to make efforts and mitigate the course of sovietization policy, and his proposals to write into the agenda some elements of national communism seemed to the leaders of the Central Committee of the All-Soviet Union Communist party (bolsheviks) not just unnecessary but even hazardous. J. Paleckis’s attitude did not comply with provisions and interests of the authorities in the Kremlin, therefore, his efforts were not supported and were valued only negatively. On the other hand, the line of sovietization of Lithuania, to which A. Sniečkus adhered and his methods of governing the party, substantially coincided with the principal position of the authorities of the USSR, as well as with the general line of the Communist party, and, therefore, a prospect of losing the post of the first secretary of the Central Committee of the Lithuanian Communist party was negligible. J. Paleckis‘s efforts to compete with A. Sniečkus strengthened the authority of the latter. The first secretary of the Central Committee of the Lithuanian Communist party deliberately avoided taking considerable sanctions against J. Paleckis, he did not seek to dismiss J. Paleckis from the position occupied. This would have not been beneficial to A. Sniečkus, because a potential strike from Moscow could be directed against J. Paleckis, a “nationalist” and “heretic”. If J. Paleckis had been removed from the political arena, nobody would have covered A. Sniečkus against potential Moscow repressions. Continuous stress caused by confrontation with J. Paleckis allowed A. Sniečkus to manifest himself as a flawless implementer of political line of the Centre and, because of this, to enhance his position as the first secretary of the Central Committee of the Lithuanian Communist party.